Direct pulp capping with mineral trioxide aggregate in a primary molar: a case report - O. BODEM, S. BLUMENSHINE, D. ZEH & M. J. KOCH (Paediatric Dentistry, 2004)
A case is presented in which pulp capping was performed on a right first mandibular primary molar in a 7-year-old male patient. An alkaline cement powder based on mineral trioxide aggregate (MTA) was used for pulp capping.